Acceptance of COVID-19 vaccine and pattern of side effects in Nepalese context: a post-vaccine cross-sectional study among health care workers in a tertiary care hospital - Adhikari, Parash; Adhikari, Kishor; Gauli, Basanta; Sitaula, Deekshanta (Journal of Chitwan Medical College, 2021)
Background: First phase of COVID-19 vaccination was initiated in Nepal in January 2021 targeting the frontline health care workers. Vaccine side effects have a significant role in public confidence regarding the vaccine and its uptake. We aimed to determine the acceptability and explore the side effects of first dose of ChAdOx1 nCOV-19 (Covishield) vaccine among the health care workers of Chitwan Medical College. Methods: We conducted a cross-sectional study among the health care workers at Chitwan Medical College. Total enumeration sampling technique was used and a self-constructed questionnaire was circulated among the health care workers to self-report their socio-demographic information and vaccination experience. Chi square test was done using Statistical Package for the Social Sciences version 20 for statistical analysis and p-value<0.05 was considered significant. Results: Out of 589 respondents, 537 (91.2%) had received the first dose of Covishield vaccine among which, 424 (78.9%) reported one or more side effects. Majority of them had very mild systemic side effects (55.9%) and injection site related side effects (25.2%). The side effects were more prevalent in <30 years age group than >30 years age group. Conclusions: Most of the vaccine recipients had very mild side effects which showed that Covishield vaccine has a good safety profile.